Pengembangan e-LKPD Materi Hidrokarbon Berbasis PBL untuk Melatih Kemampuan Berpikir Kritis : Penelitian - Sari Amelia Anggini; Asrial; Haryanto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The purpose of this study is to determine the conceptual feasibility and procedural feasibility of the e-LKPD developed. This study uses the Lee & Owens development model which consists of five stages, namely analysis, design, development, implementation, and evaluation. The products developed will be validated by material experts and media experts, then assessed by chemistry teachers who are then tested in small groups. The data analysis techniques used in this development are qualitative and quantitative analysis. The results of this study, namely the e-LKPD that was developed, obtained a total score of 4.47 with the category of "very decent" based on the assessment of material experts, obtained a total score of 4.11 with the category of "feasible" based on the assessment of media experts, obtained a total score of 4.8 with the category of "very feasible" based on the teacher's assessment and obtained an average score of 92.85% with the category of "very good" based on the assessment of students and obtained an average score of 91.14% with the category of "very good" based on the assessment of practicing critical thinking skills. Based on the results obtained, it can be concluded that problem-based e-LKPD to train critical thinking skills on hydrocarbon materials developed is suitable for use as teaching materials in schools.